الدلالات النفسية والاجتماعية ومظاهرها في الألفاظ والتراكيب العربية : قصيدة البردة للبوصيري أنموذجا - موسى، محمود أحمد
The aim of this research work is to manifest -clearly- the psychological and sociological connotations that prevail in the poem of purdah (al Burdah) composed by al-Imām al-Būṣīrī; Thereby putting out its features which portrays the poet’s hidden psychological potentialities that cannot be untied from the aptness versification of the poem that assisted in manifesting its values psychologically and sociologically. The circumstances of this versification did not only indicate the poem’s psychological or sociological values but; also the used terms inspires the poet’s sufferings as well as his psychological status which the researcher tried to unveil via psychoanalysis and socio-analysis means to the selected stanzas. The research proceeded to expose the psychological and sociological elements accompanying the texts that can be found in the contexts of the poem envisaging in love, remorse, fear, mess and grief terms. The researcher adopted two research methods (Descriptive and Analytical), thus: Descriptive method for exposing the trending connotation theories with specification on psychological and sociological theories and their different features. Analytical method was also used for analysing the selected versifications psychologically and sociologically. The research result shows that the relevant correlation between psychoanalysis and linguistics as well as relevant pertinence of psychoanalysis and socio-analysis, for their ability in translating individual expressions as the reactions of social influences emanating from parents, their societies or even inherited biological expressions. It also portray the correlation between the sender (of the information), the receiver and the reflecting stimuli between them.